A Heuristic Approach for Solving Robotic Assembly Line Balancing Problems - Pekin Alakoc, Nilufer; Mhalla, Hedi (Engineering, Technology & Applied Science Research, 2025)
This study, proposes a heuristic algorithm to balance Robotic Assembly Lines (RAL). A flexible line is assumed in which robots can be allocated to any station, perform any task, and have fixed setup costs. To consider both robot allocation costs and limiting the number of stations, the current work aims to minimize the system cost, which includes new station and robot allocation costs. It evaluates the performance of the algorithm with a large set of randomly generated samples and conducts statistical analyses to summarize, compare, and draw conclusions. The experimental results demonstrate the efficacy of the proposed algorithm in addressing large-scale problems in a reasonable timeframe.